2008
DOI: 10.1097/sla.0b013e31818c709a
|View full text |Cite
|
Sign up to set email alerts
|

Randomized Controlled Trial on Single Dose Steroid Before Thyroidectomy for Benign Disease to Improve Postoperative Nausea, Pain, and Vocal Function

Abstract: A preoperative single dose of steroid significantly reduced nausea, vomiting, and pain, and improved postoperative voice function within the first 48 hours (most pronounced within 16 hours) after thyroid resection; this strategy should be routinely applied in thyroidectomies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
138
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(142 citation statements)
references
References 37 publications
3
138
0
Order By: Relevance
“…These findings corroborated with the studies of Worni et al 18 In his study, he found that single preoperative dose of dexamethasone significantly reduced the incidence of PONV, pain and improved the voice function after 48 hours of thyroid resection. In another study of Fujji et al, dexamethasone found to be effective in reducing the incidence of PONV and use of analgesics in patients undergoing middle ear surgery.…”
Section: Discussionsupporting
confidence: 81%
“…These findings corroborated with the studies of Worni et al 18 In his study, he found that single preoperative dose of dexamethasone significantly reduced the incidence of PONV, pain and improved the voice function after 48 hours of thyroid resection. In another study of Fujji et al, dexamethasone found to be effective in reducing the incidence of PONV and use of analgesics in patients undergoing middle ear surgery.…”
Section: Discussionsupporting
confidence: 81%
“…Corticosteroid medications are potent inhibitors of inflammatory responses and have been used in single-dose administration during the perioperative period in thyroid surgery to significantly reduce postoperative nausea and pain. 81,203 While the mechanism by which corticosteroids exert a beneficial effect on nausea and pain is likely to be different than how they might impact voice changes that occur after thyroid surgery, the possibility exists that corticosteroids may also improve voice outcomes by preventing the development of anatomical abnormalities that might result in abnormalities of voice.…”
Section: Action Statement Profilementioning
confidence: 99%
“…81 Voice function was assessed by fundamental voice frequency, the mean fundamental frequency of a sustained "a," as well as by subjective voice function using a modified VHI and by a voice visual analog scale. Dexamethasone significantly reduced the incidence and severity of the postoperative nausea and/or vomiting (P = .001) and significantly reduced postoperative pain (P = .009).…”
Section: Action Statement Profilementioning
confidence: 99%
See 1 more Smart Citation
“…There are studies reporting that a perioperative single-dose administration of dexamethasone (8 mg) is beneficial for postoperative pain control [14,15,16]. On the other hand, Wattwil et al [12] showed that dexamethasone at 4 mg was effective for the prevention of PONV following breast surgery, but they could not demonstrate any difference in postoperative pain.…”
Section: Discussionmentioning
confidence: 99%